2012
DOI: 10.1016/j.jamcollsurg.2012.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for 30-Day Hospital Readmission among General Surgery Patients

Abstract: Background Hospital readmission within 30-days of an index hospitalization is receiving increased scrutiny as a marker of poor quality patient care. This study identifies factors associated with 30-day readmission following General Surgery procedures. Study Design Using standard National Surgical Quality Improvement Project (NSQIP) protocol, preoperative, intraoperative, and postoperative outcomes were collected on patients undergoing inpatient General Surgery procedures at a single academic center between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
384
5
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 553 publications
(441 citation statements)
references
References 21 publications
31
384
5
4
Order By: Relevance
“…we have avoided some factors identified in previous readmission studies, including socioeconomic issues and chronic diseases 10,11 . However, these studies often reviewed one type of operation [12][13][14] or were undertaken on non-UK populations [14][15][16] . This might explain why they have not demonstrated the same significance in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…we have avoided some factors identified in previous readmission studies, including socioeconomic issues and chronic diseases 10,11 . However, these studies often reviewed one type of operation [12][13][14] or were undertaken on non-UK populations [14][15][16] . This might explain why they have not demonstrated the same significance in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of all patients undergoing EGS will have a postoperative complication 15. In 2015, a study was carried out using the California State Inpatient Database that showed that 5.9% of EGS patients were readmitted within 30 days of discharge with higher rates of readmission in patients on public insurance and those with higher baseline comorbidity status, longer lengths of index hospital stay, and discharge dispositions other than home 16.…”
Section: The Presentmentioning
confidence: 99%
“…33,47 In addition to dose, prior anthracycline therapy, a history of mediastinal radiation, and elderly age are further risk factors for cardiotoxicity. 29,[45][46][47]49,50 Cytoskeletal …”
Section: Chemotherapymentioning
confidence: 99%
“…56 As noted previously, the cardiotoxicity of systemic therapies may become one of the most devastating consequences of the treatment itself, particularly when an additional comorbidity such as a history of coronary artery disease, hypertension, or smoking is added to the patient's active problem list (Table 1). 45,[56][57][58] …”
Section: Original Research and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation